Adoção de crianças e adolescentes: garantia do direito à convivência familiar e comunitária - Machado, Camila Ferreira (Universidade do Vale do Rio dos Sinos, 2013)
This Dissertation for an MA in Psychology is focused on the adoption of children and adolescents in a municipality called São Leopoldo. A quantitative study with a descriptive analysis of documents was conducted. Data were collected from all the processes of adoption which were analized in 2011, by the Childhood and Youth Forum of São Leopoldo. The procedure for data collection was guided by an instrument which gathered information concerning to the process, the biological family, the foster family and the child or adolescent. The data were processed statistically through descriptive analysis. The main results point to the lack of records related to the biological families. This fact limited knowledge of the condition of these families. The biological mothers assumed preponderantly the children's fate, whereas many fathers, although having registered the child, had secondary roles in their lives. It was found that during the transition between the breaking of family ties until the completion of the adoption process, there was significant elapsed time during which the children remained in an indefinite parental situation. The proportion of concluded adoptions processes analyzed revealed a parallel practice established by the Child and Adolescent Statute (ECA), without the monitoring of the judiciary and the interdisciplinary team. Although direct adoption is not an illegal practice, an intense caution is essential in such cases.
Keywords: Adoção; Família; Crianças e adolescentes; Adoption; Family; Children and adolescents; ACCNPQ::Ciências Humanas::Psicologia